Update standard model of internal control MECI 2014 (2015)
This essay tries to describe and criticize various aspects, strategies, columns and updated practices with respect to the Standard Model of Internal Control, hereinafter point out as METI, which had a recent reform of the Administrative Department of Public Service by Decree 943 of 2014, in which key concepts and techniques learned from the COSO (Committee of Sponsoring Organizations of the Treadway Commission) which have been implemented the Internal Control System of Public Entities that organize and establish their own processes relate been providing strategies, evaluation and control of public management. Therefore this essay seeks to establish the degree of strengthening qualitative level management in public institutions by updating the Standard Model of Internal Control which is mandatory for the implementation of the Internal Control System.